Practising in a pandemic: A real time study of primary care practitioners' experience of working through the first year of COVID-19 - Burn, Emily; Smith, Judith; Fisher, Rebecca; Locock, Louise; Shires, Kirsty (Frontiers in Sociology, 2022)
This article presents reflections on the lessons learnt from developing and initiating a rapid research project in four weeks during the first year of the COVID-19 pandemic. The article highlights the importance of selecting methods appropriate to rapid research, discusses the challenges of data collection in a shifting context, and the importance of the research team being prepared to cede some degree of control over the data collection process. To protect staff and patients and prevent the spread of COVID-19, general practice shifted to remote service delivery and consultations occurred via the telephone or online platforms. In the study, submissions were collected from those working in general practice to capture their experiences of the first year of the COVID-19 pandemic. Participants could choose how to submit their narratives, with some preferring to be interviewed and others contributing self-recorded submissions. This article offers practical reflections in response to the challenges of carrying out rapid research during a pandemic, including the importance of constructing a research team which can respond to the demands of the study, as well as the benefits of an expedited ethical review process. The study highlighted the importance of selecting appropriate methods to facilitate the rapid collection of data. In particular, the authors reflect on the differences between participants’ response to interviews, written submissions, and audio diaries. Open approaches to data collection were found to encourage participation and reflexivity and also generated rich narrative accounts. Rapid research has progressed our understanding of general practice’s experience of the first year of COVID-19.